The role of the microRNA-146a/complement factor H/interleukin-1β-mediated inflammatory loop circuit in the perpetuate inflammation of chronic temporal lobe epilepsy - Tao-Ran Li; Yan-Jie Jia; Chao Ma; Wen-Ying Qiu; Qun Wang; Xiao-Qiu Shao; Rui-Juan Lv (The Company of Biologists, 2018)
Increasing evidence indicates that neuroinflammation plays a crucial role in the pathogenesis of temporal lobe epilepsy (TLE). However, it is unclear how the perpetuate inflammation develops. Some recent studies have suggested the possible involvement of microRNA-146a (miR-146a) in the modulation of inflammatory signaling occurring in TLE. To understand how miR-146a modulates inflammatory signaling in TLE, we investigated the role of interleukin-1β (IL-1β), miR-146a and human complement factor H (CFH) in the perpetuate inflammation in rat models of chronic TLE and U251 cells. We found that enhancive miR-146a could upregulate the expression of IL-1β and downregulate the expression of CFH, whereas reductive miR-146a could downregulate the expression of IL-1β and upregulate the expression of CFH, in hippocampi of chronic TLE rat models. Meanwhile, enhancive miR-146a could increase the abnormal wave forms in the chronic TLE rat models. Additionally, enhancive IL-1β could feedback downregulate the expression of CFH, upregulate the expression of miR-146a and increase the abnormal wave forms in chronic TLE rat models. After CFH gene knockdown in U251 cells, enhancive miR-146a did not upregulate the expression of IL-1β. In summary, this study shows that enhancive miR-146a can upregulate the inflammatory factor IL-1β in chronic TLE by downregulating CFH, and that upregulation of IL-1β plays an important feedback-regulating role in the expression of miR-146a and CFH, forming a miR-146a-CFH-IL-1β loop circuit that initiates a cascade of inflammation and then leads to the perpetuate inflammation in TLE. Therefore, modulation of the miR-146a-CFH-IL-1β loop circuit could be a novel therapeutic target for TLE.